The need for electronic games to support student involvement and concentration in learning - zakirman zakirman; Widiasih Widiasih; Rika Aprianti; Khoirotun Nadiyyah (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2023)
The urgency of the potential use of electronic games in learning is in line with the increasingly advanced technology and as an effort to increase student engagement and concentration. Student involvement and concentration is the key so students can have a learning experience. One alternative solution is the development of electronic games to support learning. The electronic game developed in this study uses Unity software. This type of research is descriptive and qualitative and aims to describe the need for electronic games to support student involvement and concentration in learning. Data collection techniques using questionnaires. The questionnaire was made using G-Form containing 7 question items in the form of checklists or descriptions in each item answer column according to the respondent's opinion. The questionnaire was distributed online to respondents who were teachers and lecturers from various educational units in the city of Padang. Based on the study's results, electronic games are needed to increase student involvement and attention in learning activities. Games make learning fun and varied to stimulate students' interest in learning. Students with a high interest in learning will show engagement and involvement to do something diligently for a long time, be easier to concentrate, remember, and not quickly bored with what is being learned.